Effect of hydrophobic fumed silica addition on a biofilter for pentane removal using SIFT-MS. (September 2020) - González-Cortés, José Joaquín; Bruneel, Joren; Ramírez, Martín; Walgraeve, Christophe
Abstract: Biofiltration is a typical air pollution control process for the treatment of volatile organic compounds (VOCs). Mass transfer of hydrophobic VOCs to the biofilm is limited which leads to low removal efficiency (RE). Aiming to enhance the transport of hydrophobic VOCs, the effect of hydrophobic fumed silica (HFS) addition to a biofilter (BF) for pentane removal was studied in this paper. The effect of HFS on pentane removal was evaluated by daily RE measurements and periodical headspace gas pentane pulse injections using SIFT-MS as analysis apparatus. The BF was operated during more than 100 days at an empty bed residence time (EBRT) of 120 s reaching an elimination capacity (EC) up to 93.8 g pentane m −3  h −1 . At the last stage of the study, when a higher nutrient pulse and HFS to a concentration of 1.5% w/w wet were added, the BF showed better EC (46.3 ± 14.9 g pentane m −3  h −1 ; RE = 96.2%) compared to the previous stages (28.3 ± 4.4 g pentane m −3  h −1 ; RE = 68.3%). This overall performance improvement was in line with the short peak perturbation experiments carried out during the operational time which demonstrated, by net retention time (NRT) determination, to be a fast and reliable tool to gain insights into the behaviour of pollutants inside the BF and its state. Pentane demonstrated to have larger interactions with the packing material when HFS was added. NRT/EBRT ratio variated along the whole operational time, being larger at the last stage. Highlights: Addition of 1.5% w/ww HFS and nutrients enhanced pentane removal in a BF. NRT/EBRT ratio stands as a novel tool to study the BF performance. Pentane RE can be determined by peak perturbation experiments using the NRT. Constant ECs were obtained at EBRTs higher than 120 s. A maximum EC of 93.8 g pentane m −3  h −1 (RE 91%) was reached at an EBRT of 120 s.